Genes required for embryonic muscle development in Drosophila melanogaster: A survey of the X chromosome. - Drysdale, R.A.; Rushton, E.; Bate, M. (Roux's Archives of Developmental Biology, 1993)
We have begun a genetic analysis to dissect the process of myogenesis by surveying the X chromosome of Drosophila melanogaster for mutations that affect embryonic muscle development. Using polarised light microscopy and antibody staining techniques we analysed embryos hemizygous for a series of 67 deletion mutations that together cover an estimated 85% of the X chromosome, or 16.5% of the genome. Whereas the mature wild type embryo has a regular array of contractile muscles that insert into the epidermis, 31 of the deletion mutants have defects in muscle pattern, contractility or both, that cannot be attributed simply to epidermal defects and identify functions required for wild type muscle development. We have defined mutant pattern phenotypes that can be described in terms of muscle absences, incomplete myoblast fusion, failure of attachment of the muscle to the epidermis or mispositioning of attachment sites. Thus muscle development can be mutationally disrupted in characteristic and interpretable ways. The areas of overlap of the 31 deletions define 19 regions of the X chromosome that include genes whose products are essential for various aspects of myogenesis. We conclude that our screen can usefully identify loci coding for gene products essential in muscle development.